Determinants of Capital Structure:Evidence from UK Firm Panel Data - SONG, PING (2015)
This study investigates the factors that determine firms’ the capital structures in the UK market. There 139 firms, in total, listed on FTSE 100 and FTSE 250 have been used as the sample set, and a 10-year time scale, from 2004 to 2013, is selected to constitute the panel data. Both firm-specific and macroeconomic determinants are included to be investigated whether they would pose impacts on total, long term and short term debt issuance. The fixed effects regression model is adopted to estimate the relation between dependent and explanatory variables. Overall, the results obtained in this study are consistent with previous studies. The profitability, non-debt tax shields and the GDP growth rate are negatively related to all three debt ratios. In contrast, the growth opportunity and the other macroeconomic factor nominal interest rate are found to exert positively effects on these three gearing ratios. The remaining factors show mixed results. Indeed, the tangibility and firm size positively correlate to the total and long term debt ratios, while the relationship is negative with short term debt ratio. Moreover, firm’s liquidity inversely correlates with total and long term debt ratios, but depicts a positive relationship with long term gearing ratio. In addition, this study also attempt to control the effect of financial crisis by adding a time dummy variable, and the results show that when only consider the firm-specific factors, during the crisis, firms tend to augment all three debt ratios. But when the macro effects are taken into account, although the crisis also positively impact on all three ratios, only the total debt ratio shows a significant increase.